2020
DOI: 10.1016/j.jtho.2019.11.013
|View full text |Cite
|
Sign up to set email alerts
|

The International Association for the Study of Lung Cancer Thymic Tumors Staging Project: The Impact of the Eighth Edition of the Union for International Cancer Control and American Joint Committee on Cancer TNM Stage Classification of Thymic Tumors

Abstract: Objectives: The International Association for the Study of Lung Cancer Staging and Prognostic Factors Committee-Thymic Domain conducted a web-based cross-sectional survey to assess the acceptance of the TNM thymic staging system in the thoracic community.Methods: A 50-item, web-based questionnaire was circulated among the members of the major thymic organizations worldwide from September to December 2018. The survey consisted of six sections (general information; overall perception of the TNM system; pretreatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 32 publications
1
34
0
1
Order By: Relevance
“…Thymomas comprise tumor and normal cells. In particular, type B thymomas consist of a significant proportion of lymphocytes [ 15 , 16 ]. Contamination with normal cells reduces the probability of detecting mutations in tumor cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thymomas comprise tumor and normal cells. In particular, type B thymomas consist of a significant proportion of lymphocytes [ 15 , 16 ]. Contamination with normal cells reduces the probability of detecting mutations in tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…We obtained written informed consent for genetic research from all the patients in accordance with the protocols approved by the Institutional Review Board at our hospital (Institutional Review Board at Yamanashi Central Hospital). The specimens were categorized histologically based on the classification guidelines by the World Health Organization [ 16 , 27 ], and staged according to the Masaoka staging system [ 7 , 15 , 28 ]. Sections of formalin-fixed and paraffin-embedded tissues were stained with hematoxylin-eosin and microdissected using the ArcturusXT laser-capture microdissection system (Thermo Fisher Scientific, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Although long-term survival may be observed after complete surgical treatment, up to 50% of the tumors recur during follow-up [10]. Hence, several studies tried to identify pathological [11], radiological [9] and bio-humoral [12] features able to predict the risk of relapse after surgical treatment. Differentiated approaches in terms of extent of surgical resection and nodal dissection according to tumor stage and histology have been suggested [13], and therefore an accurate preoperative assessment is mandatory to correctly define the surgical strategy.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the fact that the current TNM staging system does not differentiate between encapsulated tumors and tumors invading the thymic tissue or mediastinal fat, all classified in stage I. However, it is noteworthy that a recent survey carried out in high-volume thymic-specialized European, American and Asian centers [11] showed that capsular infiltration may still play a prognostic role, and this issue should be specifically dealt with in the definition of the ninth edition of TNM staging system.…”
Section: Discussionmentioning
confidence: 99%
“…We provide blocks with "key-blocks" in order to evaluate the tumor and its surrounding tissue for accurate staging (37). Anterior mediastinal lymph nodes are also included in the sampling, because they are usually removed by the surgeons together with the fat tissue of the anterior mediastinum (52). In surgically treated THY cases at IRE, we found a metastasis in only one case, in a laterocervical lymph node (53), which developed 9 years from the original diagnosis.…”
Section: Pathological Tet Evaluation and Research Activitiesmentioning
confidence: 99%